Ekspresi dan Representasi Budaya Perempuan Muslim Kelas Menengah di Surabaya - Rofhani Rofhani (Islamica: Jurnal Studi Keislaman, 2017)
This article discusses Islamic culture that undergoes shift in meaning as a form of expression and self-representation of Middle Class Muslim Women. Basically, the religious movement of women constitutes a form of identity assertion. The Middle Class Muslim Women unconsciously exhibit new culture, although it must be admitted that not all Middle Class Muslims in Indonesia follow popular lifestyle. Instead, they demonstrate culture different from what of fundamentalist groups with their turban, cloak, and veil of a specific color. Middle Class Muslim Women create an alternative lifestyle which conforms Islamic norms, flexible, not rigid to build Islamic identity. In general, Middle Class Muslim Women in Surabaya have a relatively similar lifestyle. They tend to be rationalistic in understanding religion. They prefer, for example, more scientific materials to enrich their religious knowledge. Although they are rationalistic and follow the values of modernity, they still adhere to normative values of religion. The ethical values or religious norms are their main guideline for behavior including the reason for wearing Muslim clothing and veil.